The relationship between sitting posture and neck pain incidence in educational staff at the Universitas Muhammadiyah Surakarta - Bima Lesmana Putra; Arif Pristianto (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: While working, many educational staffs complain about musculoskeletal problems due to sitting for an extended periods. Sitting posture affects neck pain because the pressure on the intervertebral disc is twice as great when sitting compared to standing. A good sitting posture is to relax momentarily because the muscles experience tension, reducing neck pain. Methods: This cross-sectional study was carried out in December 2022 with a population of Educational Staff at the Universitas Muhammadiyah Surakarta who met the inclusion and exclusion criteria. The sampling technique in this study was purposive sampling, and 84 samples were obtained. The research data were collected by broadcast email, WhatsApp messages, and direct distribution to staff. Data were analyzed with SPSS 25.0 to determine the correlation between sitting posture and the incidence of neck pain. Results: The Spearman Rho test analysis showed a p-value<0.05, indicating a significant relationship between sitting posture and neck pain among educational staffs at the Universitas Muhammadiyah Surakarta. In contrast, the correlation coefficient showed 0.452, indicating a moderate correlation between sitting posture and neck pain. The relationship was in positive value so that the level of neck pain was reduced. Conclusion: The sitting posture is related to neck pain incidence among academic staff at the Universitas Muhammadiyah Surakarta. This study has an excellent impact on observing the factors contributing to neck pain incidence in academic staff at the Universitas Muhammadiyah Surakarta. In contrast, the further study requires finding the other aspects of neck pain in teams to minimize the occurrence of complaints in the future.